An update on FIV and FeLV test performance using a Bayesian statistical approach - Pinches, Mark D G (Veterinary clinical pathology, 2007)
BACKGROUND: Screening tests for feline retroviruses are thought to have high sensitivity and specificity, although previous studies that evaluated these tests have limitations. Novel statistical approaches have been developed that allow the estimation of sensitivity and specificity in situations where the true state of the disease in individual animals cannot be assured